A smoothed particle hydrodynamics study of ship bow slamming in ocean waves - Veen, Daniel John (Curtin University, 2010)
Smoothed Particle Hydrodynamics (SPH) is a mesh-free Lagrangian computational method suited to modelling fluids with a freely deforming surface. This thesis describes the development, validation and application of a two-dimensional Smoothed Particle Hydrodynamics algorithm to the problem of ship bow slamming in regular ocean waves. Slam events often occur in rough seas and have the potential to cause significant structural and payload damage due to the loads and subsequent whipping experienced by the ship. SPH is well suited to modelling ship bow slamming because the interaction between the bow of the ship and the water surface is of a freely deforming transient nature.The developed SPH algorithm was subjected to an extensive validation using both analytical and experimental data as a basis for comparison. The influence of each numerical correction – necessary for SPH stability – was evaluated using two theoretical problems free from the influence of external forces: the evolution of initially circular and square patches of fluid. Solid boundaries treated by the ghost particle technique were introduced and evaluated by way of the hydrostatic tank and the two-dimensional dam break.Still water impacts of two-dimensional wedges and hull cross-sections were simulated using the SPH algorithm and the results were compared with the experimental data of Aarsnes (1996), Whelan (2004) and Breder (2005). The complexity of the slamming problem was then increased by imposing the relative vertical velocity profile (between the hull and the water surface) measured during the ocean wave basin experiments of Hermundstad and Moan (2005) on a hull cross-section. Reasonable agreement between the simulated and experimental slamming pressures confirmed that the two-dimensional SPH algorithm could be applied to a three-dimensional problem through the use of a relative vertical velocity profile.Finally, the commercial ship motion prediction software SEAWAY and the validated SPH algorithm were combined in a 2D + t method to simulate bow slamming of a slender hull. The relative motion between the bow and the free water surface was extracted from the ship motion data and then imposed on a cross-section of a given hull form. Satisfactory agreement with the peak pressures measured on a model V-form hull in regular waves (Ochi, 1958) demonstrated that the developed two-dimensional SPH code is capable of modelling three-dimensional ship bow slamming.